Specifika edukace romských žáků se sluchovým postižením - Mariáková, Kristýna (2017)
The Diploma thesis „Specifics of Education of Romany Pupils with Hearing Impairment“ deals with the educational processes used in the education of Romany pupils with hearing impairment. The theoretical part presents a description of the educational constructs of the Czech educational system. This part also makes use of the term pupil with educational needs, and concepts of disability and social disadvantage are compared. Furthermore, the theoretical part also deals with the issue of education of both Romany pupils and pupils with hearing impairment. The empirical part analyses the results of the mixed research where an online survey provided a basis for conducting a qualitative research. The realized interviews were analyzed using grounded theory methodology. The aim of this diploma thesis to identify the specifics of educational process of the target group and also a further analysis of the educational strategies which are implemented by pedagogical workers.